Pengaruh Penambahan Ampas Kopi Terhadap Uji Organoleptik Cookies Berbahan Dasar Tepung Ubi Jalar Ungu : The Effect of Spent Coffee Grounds Addition on the Organoleptic Test of Cookies Made from Purple Sweet Potato Flour - Ali, Fandyka Yufriza; Hasanah, Hasanah; Kusumaningtyas , Rizky Nirmala; Asmono, Sepdian Luri (Jurnal Ilmiah Pangan Halal, 2025)
Cookies are commonly made from wheat flour, which contains gluten and relies on imports. As an alternative, this study utilizes purple sweet potato flour and coffee grounds to produce healthier and more environmentally friendly cookies. The research aims to examine the effect of coffee grounds addition on the organoleptic characteristics of cookies and determine the most preferred formulation by consumers. The study used a Randomized Block Design (RBD) with five treatments: without coffee grounds (P1), and with 2.5% (P2), 5% (P3), 7.5% (P4), and 10% (P5) coffee grounds. Organoleptic testing was conducted by 30 panelists. The results showed that the addition of coffee grounds had a significant effect (p<0.05) on texture and taste parameters, but no significant effect on color, aroma, and overall acceptance. The best treatments were P4 (7.5%) and P5 (10%), which received the highest scores in taste and texture. In conclusion, cookies made from purple sweet potato flour with up to 10% coffee grounds are acceptable to consumers and have the potential to become a functional food product based on local ingredients.